Customer's evaluation and satisfaction towards TH Hotel Kota Kinabalu / Fazilah Musa - Musa, Fazilah (2015)
Customer evaluations mean that how the customer perceives service delivery to describe their satisfaction. That customer satisfaction is a function of service performance relative to the customer evaluation. For this reason, it is important to understand how customer evaluation is formed in order to identify the factors of customer's satisfaction towards TH Hotel Kota Kinabalu. As different customers have different expectations, based on their knowledge of a product or service Reisig & Chandek (2001 ). This can be implied that a customer may estimate what the service performance will be or may think what the performance ought to be. If the service performance meets or exceeds customers' expectation, the customers will be satisfied. Previous research explored customer satisfaction regarding the service quality of all areas in the hotel so that the hotel can assess the customer perception. The results of this quantitative assessment of service quality might provide some insights into how customers rate the service quality and assessed customers' satisfactions.